Effect of the grafting ratio of poly(N‐isopropylacrylamide) on thermally responsive polymer brush surfaces. Issue 2 (16th December 2016) - Shen, Yangyang; Dong, Lianqing; Liang, Yanli; Liu, Zongjian; Dai, Rongji; Meng, Weiwei; Deng, Yulin
Abstract : Four kinds of poly( N ‐isopropylacrylamide)‐grafted silicas with different grafting ratios and the same grafting density were prepared by atom transfer radical polymerization. The chemical groups in the stationary phase was verified by FTIR spectroscopy, and the content of elements was measured by elemental analysis. The grafting ratio of thermoresponsive chromatographic materials was measured by thermogravimetric analysis and was 2.36–21.10% mg/m 2 . The retention behaviors of the stationary phase with different grafting ratios were evaluated by separating five kinds of steroids and ten kinds of different hydrophobic properties compounds. With the increase in grafting ratio, the retention time of analytes was prolonged in high‐performance liquid chromatography. The results showed that grafting ratio had a significant influence on the separation effect under the same grafting density. And the optimal grafting ratio of poly( N ‐isopropylacrylamide) was 5.81–13.15%.